2020
DOI: 10.1002/ece3.6206
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analyses reveal the molecular mechanism governing shade tolerance in the invasive plant Solidago canadensis

Abstract: Solidago canadensis is an invasive plant that is capable of adapting to variable light conditions. To elucidate the shade tolerance mechanism in S. canadensis at the molecular level, transcriptome analyses were performed for leaves growing under natural light and three shade level conditions. Many differentially expressed genes (DEGs) were found in the comparative analysis, including those involved in photosynthesis, antioxidant, and secondary metabolism of phenol‐ and flavonoid‐related pathways. Most genes en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…The enrichment of unique gene families in the photosynthesis pathway reflects the importance of photosynthesis in the invasion and adaptation of M. micrantha. Similarly, the upregulation of genes related to photosynthesis promotes the adaptation of Solidago canadensis to a shaded habitat, greatly improving the plant's ability to adapt to different light conditions [93]. The identification of unique gene families in M. micrantha with functional importance will provide a valuable resource for further research on the adaptive mechanisms of this species.…”
Section: Genes Unique To M Micrantha May Be Important For Adaptationmentioning
confidence: 99%
“…The enrichment of unique gene families in the photosynthesis pathway reflects the importance of photosynthesis in the invasion and adaptation of M. micrantha. Similarly, the upregulation of genes related to photosynthesis promotes the adaptation of Solidago canadensis to a shaded habitat, greatly improving the plant's ability to adapt to different light conditions [93]. The identification of unique gene families in M. micrantha with functional importance will provide a valuable resource for further research on the adaptive mechanisms of this species.…”
Section: Genes Unique To M Micrantha May Be Important For Adaptationmentioning
confidence: 99%
“…Zaman et al (2022) stated that different shade nets increased the physiological and biochemical attributes of C. sinensis (Zaman et al, 2022). Recently, a few studies were published on plant response to the shading on gene and transcriptional expression levels (Wu et al, 2020;Fang et al, 2022). The study of Wu et al (2022) revealed that under three shading conditions compared to no-shade control plants, the phenotypic, physiological, and photosynthetic DEGs were enhanced in Sambucus canadensis (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few studies were published on plant response to the shading on gene and transcriptional expression levels (Wu et al, 2020;Fang et al, 2022). The study of Wu et al (2022) revealed that under three shading conditions compared to no-shade control plants, the phenotypic, physiological, and photosynthetic DEGs were enhanced in Sambucus canadensis (Wu et al, 2020). The authors also observed that the DEGs linked with photosynthesis, secondary metabolites, and other hormones were affected in shading groups compared to no-shade control plants.…”
Section: Introductionmentioning
confidence: 99%
“…Because photosynthesis is the main driving force of plant nutrient accumulation, plants produce organic matter through photosynthesis, and this matter is transported to different metabolic sinks and transformed into different metabolites ( Li et al, 2017 ). In the plant response to light intensity, the shading of plants appropriately can effectively prevent excessive energy formation in seedlings, effectively promote the growth and development of plants and maintain their morphology ( Wu et al, 2016 , 2020 ). However, long-term shading will also affect the growth and development of plants; thus, moderate shading is more conducive to plant regeneration, reproduction and progressive succession ( Feng and Van Kleunen, 2014 ).…”
Section: Introductionmentioning
confidence: 99%